Identification of potential pathogenic targets and survival strategies of Vibrio vulnificus through population genomics - Zhang, Jia-Xin; Yuan, Yuan; Hu, Qing-hua; Jin, Da-zhi; Bai, Yao; Xin, Wen-Wen; Kang, Lin; Wang, Jing-Lin (Frontiers in Cellular and Infection Microbiology, 2023)
Vibrio vulnificus, a foodborne pathogen, has a high mortality rate. Despite its relevance to public health, the identification of virulence genes associated with the pathogenicity of currently known clinical isolates of V. vulnificus is incomplete and its synergistic pathogenesis remains unclear. Here, we integrate whole genome sequencing (WGS), genome-wide association studies (GWAS), and genome-wide epistasis studies (GWES), along with phenotype characterization to investigate the pathogenesis and survival strategies of V. vulnificus. GWAS and GWES identified a total of six genes (purH, gmr, yiaV, dsbD, ramA, and wbpA) associated with the pathogenicity of clinical isolates related to nucleotide/amino acid transport and metabolism, cell membrane biogenesis, signal transduction mechanisms, and protein turnover. Of these, five were newly discovered potential specific virulence genes of V. vulnificus in this study. Furthermore, GWES combined with phenotype experiments indicated that V. vulnificus isolates were clustered into two ecological groups (EGs) that shared distinct biotic and abiotic factors, and ecological strategies. Our study reveals pathogenic mechanisms and their evolution in V. vulnificus to provide a solid foundation for designing new vaccines and therapeutic targets.